La literalidad interpretada desde la coherencia del sistema. Las relaciones entre el Reglamento Bruselas I y los convenios sobre materias particulares según el TJUE - Garau Sobrino, Federico F. (CUADERNOS DE DERECHO TRANSNACIONAL, 2011)
Article 71 of Brussels I Regulation not affect any conventions on particular matters in which the Member States are parties. However, the rules governing jurisdiction, recognition and enforcement of judgments that are laid down by a specialised convention cannot compromise the principles which underlie judicial cooperation in civil and commercial matters in the European Union. Thus, the wording of Article 71 must be interpreted taking into account the consistency of the system.